Meta-analysis to implement alpha-synuclein in extracellular vesicles as a potential biomarker for parkinson's disease - Víctor H. Juárez-Vaquera; Marcos F. Rosetti-Sciutto; Valeria Morales-Ruiz; Laura V. Adalid-Peralta (Permanyer, 2023)
Background: In Parkinson's disease (PD), exosomes carry α-synuclein (α-syn), a fibrillar protein aggregates with potential value as a biomarker. Objective: Evidence on blood levels of exosomal α-syn in PD patients and controls was reviewed for their consistency. Methods: Thirty-six studies on exosomal α-syn concentrations in PD were identified in a systematic literature search and meta-analysis. Results: Both raw and ratio-adjusted blood exosomal α-syn levels were consistently higher in PD patients than in controls. The standardized mean difference (SMD) was 1.54 (0.18-2.90, CI95%, p < 0.01) and 1.53 (0.23-2.83, CI95%, p < 0.01), respectively. Conclusion: Our results suggest that exosomal α-syn concentrations could be a useful biomarker for PD.